(untitled) (KULT_online, 2025)
Remedios Zafra’s El Informe, an essay on intellectual labor and the meaning of writing, compels us to think about the conditions under which we research. Through narrative digressions, Zafra condemns the effects of liberalization on the bodies and minds of researchers and writers. The essay illustrates scholars’ affections and losses within the bureaucratic machinery. In other words, it is a manifesto against mechanical labor. It is a valuable read for those on the verge of burnout.